"The simple life experiences that every other human gets": Desire for normalcy among adolescents and young adults with advanced cancer. Issue 1 (29th October 2022) - Umaretiya, Puja J.; Fisher, Lauren; Altschuler, Andrea; Kushi, Lawrence H.; Chao, Chun R.; Vega, Brenda; Rodrigues, Gilda; Josephs, Isabel; Brock, Katharine E.; Buchanan, Susan; Casperson, Mallory; Fasciano, Karen M.; et al.
Abstract: Background: Adolescents and young adults (AYAs) with advanced cancer identify normalcy as an important component of quality end‐of‐life care. We sought to define domains of normalcy and identify ways in which clinicians facilitate or hinder normalcy during advanced cancer care. Procedure: This was a secondary analysis of a qualitative study that aimed to identify priority domains for end‐of‐life care. Content analysis of semi‐structured interviews among AYAs aged 12–39 years with advanced cancer, caregivers, and clinicians was used to evaluate transcripts. Coded excerpts were reviewed to identify themes related to normalcy. Results: Participants included 23 AYAs with advanced cancer, 28 caregivers, and 29 clinicians. Participants identified five domains of normalcy including relationships, activities, career/school, milestones, and appearance. AYAs and caregivers identified that clinicians facilitate normalcy through exploration of these domains with AYAs, allowing flexibility in care plans, identification of short‐term and long‐term goals across normalcy domains, and recognizing losses of normalcy that occur during cancer care. Conclusions: AYAs with cancer experience multiple threats to normalcy during advanced cancer care. Clinicians can attend to normalcy and improve AYA quality of life by acknowledging these losses through ongoing discussions on how best to support domains of normalcy and by reinforcing AYA identities beyond a cancer diagnosis.